Optimalisasi peran guru dalam deteksi dini hambatan belajar dan perkembangan anak di taman kanak-kanak - Rr. Retno Handasah; Sally Putri Karisma; Yuliana Yuliana; Praditya Nur Rizki Adriana Putri (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2026)
Early identification of learning barriers and developmental delays during the preschool years determines whether children receive timely stimulation, yet many early childhood educators in eastern Indonesia lack structured knowledge of developmental indicators and screening procedures. This community service programme aimed to strengthen the capacity of kindergarten teachers to recognise early signs of learning and developmental difficulties and to act on them collaboratively with parents. The activity was conducted at TK Kemala Bhayangkari 04 Sentani, Jayapura Regency, Papua, and involved forty kindergarten teachers. The intervention combined a seminar on child growth, development and learning barriers, a demonstration of simple observation and screening instruments, and a moderated sharing session. Evaluation employed a knowledge pre-test and post-test, a satisfaction questionnaire, structured observation, and documentation. Mean knowledge scores rose from 59.00 to 79.00, a normalised gain of 0.49 in the moderate category, and the difference was statistically significant with a large effect size. All participants reached the mastery threshold after the seminar; 80% reported heightened awareness of early detection as a core professional role; 75.3% showed improved ability to identify early warning signs; and 84.5% expressed satisfaction. The programme yielded a teacher-parent collaborative framework that the partner school can institutionalise for routine developmental monitoring